Connected : Or What It Means To Live In The Network Society - Shaviro, Steven (Book collections on Project MUSE., 2003)
Annotation "Connected is made up of a series of mini-essays - on cyberpunk, hip-hop, film noir, Web surfing, greed, electronic surveillance, pervasive multimedia, psychedelic drugs, artificial intelligence, evolutionary psychology, and the architecture of Frank Gehry, among other things. Shaviro argues that our strange new world is increasingly being transformed in ways, and by devices, that seem to come out of the pages of science fiction, even while the world itself is becoming a futuristic landscape. The result is that science fiction provides the most useful social theory, the only form that manages to be as radical as reality itself." "Connected looks at how our networked environment has manifested itself in the work of J.G. Ballard, William S. Burroughs, Philip K. Dick, William Gibson, K.W. Jeter, and others. Shaviro focuses on science fiction not only as a form of cultural commentary but also as a prescient forum in which to explore the forces that are morphing our world into a sort of virtual reality game. Original and compelling, Connected shows how the continual experimentation of science fiction, like science and technology themselves, conjures the invisible social and economic forces that surround us."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved